Genome-wide scan reveals population stratification and footprints of recent selection in Nelore cattle - Cardoso, Diercles F. [UNESP]; Albuquerque, Lucia Galvao de [UNESP]; Reimer, Christian; Qanbari, Saber; Erbe, Malena; Nascimento, Andre V. do [UNESP]; Venturini, Guilherme C. [UNESP]; Becker Scalez, Daiane C. [UNESP]; Baldi, Fernando [UNESP]; Ferreira de Camargo, Gregorio M. [UNESP]; Zerlotti Mercadante, Maria E.; Santos Goncalves Cyrillo, Joslaine N. do; et al. (Biomed Central Ltd, 2018)
Background: This study aimed at (1) assessing the genomic stratification of experimental lines of Nelore cattle that have experienced different selection regimes for growth traits, and (2) identifying genomic regions that have undergone recent selection. We used a sample of 763 animals genotyped with the Illumina BovineHD BeadChip, among which 674 animals originated from two lines that are maintained under directional selection for increased yearling body weight and 89 animals from a control line that is maintained under stabilizing selection. Results: Multidimensional analysis of the genomic dissimilarity matrix and admixture analysis revealed a substantial level of population stratification between the directional selection lines and the stabilizing selection control line. Two of the three tests used to detect selection signatures (F-ST, XP-EHH and iHS) revealed six candidate regions with indications of selection, which strongly indicates truly positive signals. The set of identified candidate genes included several genes with roles that are functionally related to growth metabolism, such as COL14A1, CPT1C, CRH, TBC1D1, and XKR4. Conclusions: The current study identified genetic stratification that resulted from almost four decades of divergent selection in an experimental Nelore population, and highlighted autosomal genomic regions that present patterns of recent selection. Our findings provide a basis for a better understanding of the metabolic mechanism that underlies the growth traits, which are modified by selection for yearling body weight.